Serviço de Atendimento Móvel de Urgência: vigilância auditiva e visual na ótica dos profissionais - Marina Amazildes Rocha (2015)
The Mobile Emergency Care Service (SAMU) is privileged locus of visibility allowing surveillance continues in the work and the movement of professionals and ambulances. The use of equipment such as telephone, radio, GPS type tracking systems allow the permanent contact of Regulation Center with teams in attendance and access all the information conveyed between. The population, in turn, follows the movement of ambulances and professionals, as well as the services rendered. This explicit or implicit surveillance, while curtails freedom for SAMU crews also enables the maintenance of the effects of disciplinary power on them and their behavior. The study aimed to analyze the configuration of surveillance in view of the SAMU professionals and interference in daily work. A qualitative case study was conducted. Data were collected through semi-structured interviews with 13 professionals from SAMU municipality of Contagem, the ethical principles being met. The interviews were subjected to content analysis. The results showed that the professionals of the SAMU perceive themselves observed all the time, especially by the population on public roads, accompanying the care and use of technology more accessible from mobile phones to photograph and film the scenes of care, either out of curiosity, why as a way of monitoring. The use of radio, telephone and GPS, the system at the touch of Regulation Center with the teams have been reported as a factor that conveys security, not being understood as a surveillance by the professionals. In this sense, the internal surveillance system does not cause discomfort to the professionals, however, external surveillance service for the population and the media scenes creates in professional higher voltage during procedures, greater concern for the judgment on its activities and even need for updating and improvement of the work done. The media exposure explores negative aspects that, true or not, hinder clarification of the service function for the population. In short, it is considered that professionals recognize the internal monitoring of SAMU as positive as they provide greater security to him, but grieve the external surveillance service, mainly in street answering scenes considering that hinder the work and criticism they are not always true for not knowing the technical work done.